MAKNA SAKURA BAGI MASYARAKAT JEPANG - Cuk Yuwana (Universitas 17 Agustus 1945 Surabaya, 2010)
Abstract. â€Sakuraâ€ derives from the word â€sakuâ€ + suffix â€raâ€.Â SakuÂ means â€to bloomâ€Â and the suffix â€raâ€ means the plural of â€sakuâ€. From this, the word â€Sakuraâ€ means the blooming flower. The flower Sakura blooms in the pring for at this season Japan is in a cold weather, around teens degree centigrate. Beside its beauty, sakura connotes a hard worker since sakura is able to overcome all the difficulties and obstacles and presents beautiful scenery at as the result. Its beauty is often compare to white, beautiful, fair, healthy, and young Japanese woman. Â Key words: Â sakura, meaning, society